Isothermal Crystallization Properties of Rbd-Palm Oil as Measured By Dsc and Oscillatory Rheometry - Bangun P. Nusantoro (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
In this research, the crystallization properties of refined bleached and deodorized (RBD) palm oil under isothermal conditions were investigated. A good quality of RBD palm oil (showed by IV, FFA content, PV, and AV with the values of 52.14, 0.06%, 1.39 meq/kg, and 0.88, respectively) was used in this research. In general, RBD palm oil demonstrat ed a twostep crystallization process at the isothermal crystallization temperatures/ of 18oC, 20oC and 22oC. From differential scanning calorimetry (DSC) measurement of RBD palm oil, the melting heats/showed decrement values (33.84 J/g, 26.83 J/g and 22.47 J/g) but the peaks of the corresponding endotherm/ showed increment values (33.52oC, 34.72oC and 36.44oC) when both were correlated to the increased values of iso thermal crystallization temperatures/ (18oC, 20oC, and 22oC, respectively). From rheometry analysis of RBD palm oil (at the isothermal crystallization temperature of 18oC), the rheograms gave the values of the phase shift angle ( ), storage modulus () and complex modulus () at the end of crystallization process as follows: 24o,11.36 kPa, and 39 kPa. The overlay of andgavewith the value of 49.6 Pa at the isothermal time of 11.7 minute.